Pertumbuhan Tanaman Sawi (Brassica juncea L.) Terhadap Aplikasi Pupuk Organik Cair - Nurhayati, Nurhayati; Khairani, Siti; Sembiring, Juhardi (JURNAL AGROPLASMA, 2024)
The mustard plant is one of the horticultural commodities that is popular with the public because it has high fiber and nutritional content so it has high economic selling value. Various cultivation techniques that can be done to increase mustard greens production are by applying liquid organic fertilizer which can increase plant growth and production. Liquid organic fertilizer is an organic fertilizer designed as a balanced food complete with macro and micro nutrients for various types of plants. This research aims to determine the effect of mustard greens growth and production on the provision of liquid organic fertilizer. This research used a non-factorial randomized block design (RAK) with 5 treatment levels. The first factor is the use of liquid organic fertilizer (P0: 0 cc/l; P1: 2 cc/l; P2: 4 cc/l; P3: 6 cc/l; P4: 8 cc/l).The results showed that liquid organic fertilizer had a significant effect on leaf area but had no significant effect on plant height. The most efficient concentration of liquid organic fertilizer for the growth and production of mustard greens is 6 cc/liter. Keywords : mustard greens, liquid organic fertilizer, growth